Impact of various progestins with or without transdermal testosterone on gonadotropin levels for non‐invasive hormonal male contraception: a randomized clinical trial. (11th February 2017) - Zitzmann, M.; Rohayem, J.; Raidt, J.; Kliesch, S.; Kumar, N.; Sitruk‐Ware, R.; Nieschlag, E.
Summary: Although several progestins have been tested for hormonal male contraception, the effects of dosage and nature of various progestins on gonadotropin suppression combined with and without additional testosterone has not been performed in a comparative trial. The aim of this study was to evaluate the differential impact of four oral or transdermal progestins on the suppression of gonadotropins in healthy men: oral: cyproterone acetate (CPA), levonorgestrel (LNG), norethisterone acetate (NETA), and transdermal: Nestorone ® (NES), all in combination with transdermal testosterone (T). Randomized clinical trial testing was performed with four progestins at two doses each. After a 2‐week progestin‐only treatment, transdermal T was added for further 4 weeks and was followed by a 3‐week recovery period. Progestin‐dose per day: CPA 10 mg/20 mg, NES 2 mg/3 mg/dose e.g. 200/300 μg/day absorbed, NETA 5 mg/10 mg, LNG 120 μg/240 μg. From an andrology outpatient clinic, 56 healthy men aged 18–50 years, with body mass index ≤33 kg × m −2 were included in the study. Serum concentrations of luteinizing hormone (LH) and follicle‐stimulating hormone (FSH) were studied. Secondary outcome measure included were serum testosterone concentrations, sperm concentrations, and safety parameters. Intergroup comparisons demonstrated that CPA and LNG had the strongest effect on LH/FSH suppression. Nevertheless, every substance showed significant inhibitory effects on gonadotropin secretion, especially in combination with transdermal T. A decrease in hematocrit and insulin sensitivity as well as cholesterol subfractions and triglycerides was uniformly seen for every group. The combination of oral or transdermal progestins with a transdermal testosterone preparation is able to suppress gonadotropins. Further dose titration studies with sperm suppression as an end‐point should be conducted to determine the lowest effective dose for hormonal male contraception.